ORIENTALISME DALAM KAJIAN KEISLAMAN: KRITIK DAN RELEVANSINYA TERHADAP PERKEMBANGAN PEMIKIRAN ISLAM MODERN - Muflih; Ridho Abdurohim; Aqiluddin Ibnu Qadir; Jemy Harto (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Orientalism, as a Western scholarly discourse on the East, particularly the Islamic world, has become one of the most debated issues in contemporary Islamic studies. This article aims to examine the genealogy of Orientalism, identify the major criticisms directed at it by both Western scholars and Muslim intellectuals, and analyze the relevance of these debates to the development of modern Islamic thought. Employing a descriptive-analytical library research method, this study finds that Edward Said's seminal work Orientalism (1978) fundamentally transformed perspectives on the epistemology of Eastern studies while encouraging Muslim intellectuals to develop a more autonomous methodology for Islamic studies. Nevertheless, this article also demonstrates that the relationship between Orientalism and Islamic studies is not entirely antagonistic. Several modern Muslim thinkers have adopted Orientalist philological and historical-critical methods to reinterpret the Islamic intellectual tradition in a more reflective and critical manner. Therefore, despite its ideological biases and colonial interests, the legacy of Orientalism continues to offer methodological contributions that cannot be entirely disregarded in shaping the discourse of modern and contemporary Islamic thought.